Monkeys and Apes and Their Relatives - Taylor, Barbara, 1954- (New York Oxford University Press, 2002)
Details about our closest relatives in the animal kingdom. This work presents: a baby marmoset hitching a ride on its mother's back, how gibbons zoom through the trees, and how a colobus monkey can sleep sitting up. It explores the differences between a selection of monkeys and apes, and some of their rare relatives such as lemurs.
Includes Colour Illustrations and Index.
At Head of Title: The Natural History Museum.
Keywords: Lizards -- Snakes -- Toads